2012
DOI: 10.1002/cbdv.201100341
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Chemotaxonomic Differentiation of Two European Dog's Mercury Species: Mercurialis annua L. and M. perennis L.

Abstract: Mercurialis annua and M. perennis are medicinal plants used in complementary medicine. In the present work, analytical methods to allow a chemotaxonomic differentiation of M. annua and M. perennis by means of chemical marker compounds were established. In addition to previously published compounds, the exclusive presence of pyridine-3-carbonitrile and nicotinamide in CH(2) Cl(2) extracts obtained from the herbal parts of M. annua was demonstrated by GC/MS. Notably, pyridine-3-carbonitrile was identified for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…A literature survey revealed that the effect of salinity on the metabolome of annual dioecious species has not been reported. A recently published research [ 59 ], comparing metabolites of medicinal interest in M. annua and M. perennis , in the context of species classification, was reported. However, gender related difference in the metabolites was not in the scope of that research.…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey revealed that the effect of salinity on the metabolome of annual dioecious species has not been reported. A recently published research [ 59 ], comparing metabolites of medicinal interest in M. annua and M. perennis , in the context of species classification, was reported. However, gender related difference in the metabolites was not in the scope of that research.…”
Section: Discussionmentioning
confidence: 99%
“…Configuration analysis was performed according to a modified literature protocol . In brief, a purified euphrasianin fraction (9.3 mg) was treated with 1 n NaOH (10 ml) and stirred at room temperature (24 h).…”
Section: Experimental Partmentioning
confidence: 99%
“…Analytic methods to allow a chemotaxonomic differentiation of these species by means of chemical marker compounds were established (Lorenz et al, 2012). Analytic methods to allow a chemotaxonomic differentiation of these species by means of chemical marker compounds were established (Lorenz et al, 2012).…”
Section: Phenolic Compoundmentioning
confidence: 99%